Socio-Economic Role of the Site Museums for Visitors and Local Communities An Applied Study on Memphis Site Museum (Mit Rahina) - Fatma Ahmed Soliman (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2022)
Museums are playing essential roles as a culture center, another role for the artifacts and objects to collect, preserve the heritage, natural history, culture, monuments at archaeological sites, and more important is the role of the museum to develop the community. More over Some museums focus on heritage protection functions by themselves, and manage the archaeological heritage of a region or nation. The research is discussing some examples of the site museums around the world with their role for their community, and it gives a survey about the different site’s museums and gives guideline for Egyptian museums to be  as a house for tangible and intangible history for all community for both national and international. This paper offers opportunity of bringing together local heritage communities and museum representation of their worlds and meaningful exhibits that both teach and promote their precious value. تعلب المتاحف أدوارًا متعددة ومختلفة من حيث تجميع وحفظ التاريخ والتراث والآثار، کما تلعب دورا فاعلًا في الثقافة والآثار بالمواقع الأثرية وتؤثر في تطوير وتنمية مجتمعاتها. نجد أن بعض المتاحف تأخذ على عاتقها مهمة حفظ الآثار وکذلک تقوم بإدارة المواقع الأثرية التراثية لمناطقها ومجتمعاتها. البحث يتناول أمثلة من متاحف المواقع حول العالم ودورها لخدمة المجتمع المحلي والعالمي وتضع خريطة طريق لمتاحف المواقع بمصر ليصبح المتحف راعيًا ومرکزًا للتاريخ الملموس والتراث الباقي وممتد منذ أقدم العصور أى ما کان سواء محليًا أو عالميًا. تقدم هذه الدراسة جمعًا ما بين قيمة وأهمية المتحف وعالمه سواء محليًا أو عالميًا وکيف يکون المتحف مرکزًا ثقافيًا لتنمية المجتمع المحيط ومتفاعلًا مع جميع الزوار.